슬관절 전치환술 후 조기 실패 분석 - 김희선(Hee Seon Kim); 민학진(Hak Jin Min); 윤의성(Ui Seoung Yoon); 서재성(Jae Sung Seo); 김윤종(Yoon Jong Kim); 임병호(Byung Ho Lim) (The journal of the Korean Orthopaedic Association, 2004)
목 적: 슬관절 전치환술 후 5년 이내의 조기 실패 원인 및 평균기간을 분석하였다. 대상 및 방법: 1994년 8월부터 2003년 5월까지 시행한 786예의 일차 슬관절 전치환술 중에서 5년 이내에 조기 실패로 재치환술을 시행한 38예를 대상으로 하였다. 여자가 36예, 남자가 2예였고 재치환술시 연령은 평균 66세였다. 원인 질환은 퇴행성 관절염이 36예로 대부분을 차지하였다. 결과 분석을 위해서 후향적으로 조기 실패의 원인과 기간 등을 조사하였다. 결 과: 조기 실패를 보인 환자의 재치환술까지의 기간은 평균 2년이었고 조기 실패의 원인으로는 폴리에틸렌의 마모가 18 예(47.4%)로 가장 많았으며 수술 후 치환물의 부정렬, 특히 경골의 절골각이 평균 5.1° 내반이었고 3° 이상의 내반을 보인 경우가 14예(82.4%)였으며 좌식생활, 재래식 화장실의 사용 등 슬관절을 과도하게 굴곡하는 일상생활을 하고 있었다. 그 외 감염이 16예(42.1%), 슬관절 불안정성이 2예(5.3%)였으며 무균성 해리 및 슬개골 삽입물의 해리가 각 1예(2.6%)였다. 결 론: 슬관절 전치환술 후 조기 실패로 재치환술을 시행한 경우는 38예 4.8%였고 실패의 가장 큰 원인은 폴리에틸렌의 마모와 감염이었다. 수술 후 치환물의 부정렬과 슬관절을 과도하게 굴곡하는 환경이 삽입물의 조기 마모와 관련되어 있을 것이라 사료되며, 당뇨병이나 장기간 스테로이드 복용 등이 감염과 연관되어 있을 것으로 생각된다. Purpose: To analyze the cause of failure and average period in patients who had revision surgery within 5 years of their primary total knee arthroplasty (TKA). Materials and Methods: 786 total knee arthroplasties were performed between August 1994 and May 2003. During the period, there were 38 cases, 36 females and 2 males, of revision surgery within 5 years. The mean age was 66 years. The most common causes of disease in revision were degenerative arthritis. We analyzed the reasons for early failure retrospectively. Results: Revision TKA were performed at average 2 years after primary TKA. The causes of revision were polyethylene wear in 18 cases (47.4%), deep infection in 16 (42.1%), instability in 2, and aseptic loosening in 1, dissociation of patella component in 1. The degree of varus in tibial cutting was 5.1° in average in polyethylene wear group. The obliquity of the tibial joint line was more than 3° varus in 14 cases (82.4%). Most patients had their knee in hyperflexion and squatting position during activities of daily living. Conclusion: Thirty eight cases (4.8%) were performed revision surgery within 5 years of primary TKA. Polyethylene wear and deep infection were the common causes of early failure of primary TKA. The component malalignment, hyperflexion and squatting position during activities of daily living may be related to polyethylene wear. Diabetes mellitus and long term steroid application, may be related to infection. KCI Citation Count: 0